Histological study of the drug PEG-Filstim sub-acute toxicity - V. L. Karbovskyy; I. A. Shevchuk; O. V. Kurkina; T. Ye. Makovska (The State Expert Center of the Ministry of Health of Ukraine, 2018)
One of the critical steps in development of safe and efficient drugs during their pre-clinical trials are toxicity studies. Therefore, the aim of our work was to study PEG-Filstim toxic effects on animal internal organs and tissues. Toxicity study of PEG-Filstim was performed in 50 white wild-type rats of both sexes with body weight of 170 to 230 g on daily (28 days) subcutaneous administration in the doses of 0.5, 1.0 and 2.0 mg/kg. In all groups of animals, after completing the experiment careful pathomorphologic and histological examination was performed. PEG-Filstim has been shown to possess no toxic effects on internal organs of laboratory rats and does not cause specific changes in the heart, kidneys and mucous coat of stomach on daily subcutaneous administration in the doses of 0.5, 1.0, and 2.0 mg/kg within 28 days. In the maximum applied dose of 2.0 mg/kg, the studied drug causes pronounced acute splenic hyperplasia, related to hyper-proliferation of the reticular tissue, leads to functional strain of the liver due to formation of hematopoietic foci in it, as well as impaired integrity of the respiratory epithelium and congestive signs in the lungs, swelling of the brain tissues, abnormalities in the gray matter structure and hyperemia of the brain vessels. These effects were not observed in the animals, to which the drug was administered in the doses of 0.5 and 1.0 mg/kg. Administration of PEG-Filstim (in all studied doses) results in increasing the size of the ankle joint in rats, which is related to hyper-proliferation of the reticular tissue, leading to bone defect formation in the form of perforation with subsequent filling the periosteum with reticular tissue and formation of hematopoietic foci within its boundaries.